Growth of tall fescue (Festuca arundinacea Schreb.) seedling sown in soil mixed with nitrogen and natural zeolite - S. Eshghi (Advances in Horticultural Science, 2014)
To determine the interaction of nitrogen and natural zeolite in culture medium on the vegetative growth of tall fescue (Festuca arundinacea Schreb.) ‘Starlet’ a greenhouse experiment was conducted. A complete randomized design with factorial arrangements including two factors (nitrogen and zeolite) was employed for each treatment with four replications. Treatments of nitrogen were 0, 0.06 and 0.12 g kg-1 in the soil mixture and treatments of zeolite were 0, 10, 20 and 30 g kg-1 in the soil mixture. Application of zeolite and nitrogen had different effects on seedling height, fresh and dry weights of clippings before first, second and third mowings, chlorophyll and nitrogen content of clippings, and dry weights of roots. Adding zeolite at the rate of 30 g kg-1 and nitrogen at the rate of 0.12 g kg-1 to culture medium significantly increased the height of turf seedlings. It is concluded that zeolite could absorb and slowly release nitrogen to the culture medium.